The dimensions, development, and deployment of strategic leader capability - Laljani, Narendra (Cranfield University, 2007)
This research – which was motivated by a perceived gap between the reality of the world of the strategic leader and leadership development practice - offers an integrated perspective on the dimensions, development, and deployment of strategic leader capability. In the first of three thematically linked projects, a conceptual framework was developed based on four key dimensions of capability: judgement, the strategic conversation, contextual mastery, and behavioural complexity. In the second project, empirical findings from in-depth qualitative interviews with individuals in strategic leadership roles corroborated and enriched the framework; highlighted the importance of informal learning; and emphasised the role of mentors and stretch assignments as formative development processes. In addition, critical reflection, through either informal or formal processes, played an important “sense-making” and developmental role. In the third project, action research involving two formal leader development interventions was undertaken with the objective of developing strategic leader capability while deliberately managing the influential development processes identified. The results indicated that while strategic leader capability can be learned, and that key development processes can be simulated with varying degrees of success, positive performance outcomes also require high self-efficacy. Based on these findings, a model is presented which links together strategic leadership capability, major development processes, self-efficacy, context, and performance outcomes. The research raises numerous interesting questions with significant implications for strategic leader performance and development, as well as the leader development industry.